Locating Jerusalem’s Royal Palace in the Second Millennium BCE in Light of the Glyptic and Cuneiform Material Unearthed in the Ophel - Na'aman, Nadav (Tel Aviv, 2023)
This article argues, on the basis of indirect evidence drawn from the results of the excavations of the Ophel, that during the second millennium BCE, the governing centre of Jerusalem was located on the Temple Mount. The conclusion rests mainly upon a numerical comparison between the glyptic material uncovered in the Ophel vis-à-vis that unearthed in the Southeastern Hill (the City of David) and upon the discovery of two fragmented cuneiform tablets in this area. It is postulated that the findings uncovered in the Ophel might serve as a litmus test for the early urban life in the Temple Mount above it. The city at the time included two distinct quarters: the Temple Mount, the seat of the king and his court, and the Southeastern Hill, consisting of the summit of the hill and the Gihon Spring. This two-part division of the city persisted from its foundation in the MB II down to the early first millennium BCE and continued until the 8th century BCE.